Allosteric modulator potentiates β2AR agonist–promoted bronchoprotection in asthma models - Ahn, Seungkirl; Maarsingh, Harm; Walker, Julia K.L.; Liu, Samuel; Hegde, Akhil; Sumajit, Hyeje C.; Kahsai, Alem W.; Lefkowitz, Robert J. (The Journal of Clinical Investigation, 2023)
Asthma is a chronic inflammatory disease associated with episodic airway narrowing. Inhaled β2-adrenergic receptor (β2AR) agonists (β2-agonists) promote — with limited efficacy — bronchodilation in asthma. All β2-agonists are canonical orthosteric ligands that bind the same site as endogenous epinephrine. We recently isolated a β2AR-selective positive allosteric modulator (PAM), compound-6 (Cmpd-6), which binds outside of the orthosteric site and modulates orthosteric ligand functions. With the emerging therapeutic potential of G-protein coupled receptor allosteric ligands, we investigated the impact of Cmpd-6 on β2AR-mediated bronchoprotection. Consistent with our findings using human β2ARs, Cmpd-6 allosterically potentiated β2-agonist binding to guinea pig β2ARs and downstream signaling of β2ARs. In contrast, Cmpd-6 had no such effect on murine β2ARs, which lack a crucial amino acid in the Cmpd-6 allosteric binding site. Importantly, Cmpd-6 enhanced β2 agonist–mediated bronchoprotection against methacholine-induced bronchoconstriction in guinea pig lung slices, but — in line with the binding studies — not in mice. Moreover, Cmpd-6 robustly potentiated β2 agonist–mediated bronchoprotection against allergen-induced airway constriction in lung slices obtained from a guinea pig model of allergic asthma. Cmpd-6 similarly enhanced β2 agonist–mediated bronchoprotection against methacholine-induced bronchoconstriction in human lung slices. Our results highlight the potential of β2AR-selective PAMs in the treatment of airway narrowing in asthma and other obstructive respiratory diseases.